If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11n-2n-2n=7
We move all terms to the left:
11n-2n-2n-(7)=0
We add all the numbers together, and all the variables
7n-7=0
We move all terms containing n to the left, all other terms to the right
7n=7
n=7/7
n=1
| 5x-10=14+2x | | -6x-5(-4x+11)=71 | | 5+2(3x-1)=4(x-2) | | 7x-4X-15)=33 | | z+4(2z=3)=15 | | 9x+25=286 | | X+5÷2+x÷3=20 | | 2g-g=3 | | 6a^2-6a-6=0 | | Y=-0.2x+1.3x | | -2x-2(3x-7)=54 | | 10×30=2x | | 2t-6=6t+12 | | 24x+7x=11950.2 | | 25r+9=10 | | x-x=x-x | | 7x-2(-7x+3)=141 | | 6y-18=-2y-10 | | -5+2x=x-8 | | 6x-8=10x=10 | | -6x+3(-3x+11)=-132 | | n+12=20(12,8,20,0) | | -6x-4(-x-14)=-36 | | 8c+9=5c-21 | | 8c+9=5c+21 | | 3x+4(-x+2)=-4 | | 3(6x+9)=4(7x+10) | | 5x+18=2(2x+8) | | -2x+6(2x+14)=-36 | | 11b-6b-3b=20 | | -3/4z=12/56 | | t=60t^2 |